Activation of extracellular signal‐regulated kinase is associated with hepatocellular carcinoma with aggressive phenotypes. Issue 3 (26th December 2019) - Minagawa, Takuya; Yamazaki, Ken; Masugi, Yohei; Tsujikawa, Hanako; Ojima, Hidenori; Hibi, Taizo; Abe, Yuta; Yagi, Hiroshi; Kitago, Minoru; Shinoda, Masahiro; Itano, Osamu; Kitagawa, Yuko; et al.
Abstract : Aim: Sorafenib inhibits multiple kinase signaling pathways, including the rat sarcoma virus (Ras)/rapidly accelerated fibrosarcoma (Raf)/mitogen‐activated protein kinase kinase (MEK)/extracellular signal‐regulated kinase (ERK) pathway, and is a promising therapy for hepatocellular carcinoma (HCC). However, the role of ERK activation in HCC remains unclear. This study was designed to investigate the potential link between ERK activation and aggressive HCC phenotypes. Methods: We evaluated nuclear ERK expression by immunohistochemistry in 154 resected HCC nodules from 136 patients. We then investigated the associations of ERK expression with the clinicopathological characteristics of HCC, c‐MET expression, and the molecular subclass biomarkers Ki‐67, keratin 19 (KRT19, CK19, or K19), and sal‐like protein 4. Multivariate Cox regression analysis was carried out to determine independent prognostic factors for overall survival and recurrence‐free survival. The effects of ERK activation by hepatocyte growth factor (HGF) on eight HCC cell lines were further examined. Results: High‐level nuclear expression of ERK was observed in 20 (13%) of 154 nodules and was significantly associated with higher serum alpha‐fetoprotein levels ( P  = 0.034), poorer differentiation ( P  = 0.003), a higher Ki‐67 index ( P  < 0.001), high‐level expression of c‐MET ( P  = 0.008), KRT19 ( P  = 0.002), or sal‐like protein 4 ( P  < 0.001), and shorter overall survival (multivariate hazard ratio 3.448; P  = 0.028) and recurrence‐free survival (multivariate hazard ratio 2.755; P  = 0.004). HCC cells treated with hepatocyte growth factor showed enhanced cell proliferation together with ERK activation and upregulated KRT19 expression, both of which were inhibited by sorafenib. Conclusions: High‐level ERK activation is associated with a KRT19‐positive highly proliferative subtype of HCC with a dismal prognosis. These findings support the key role of the hepatocyte growth factor/c‐MET/ERK axis in HCC progression.